A study on the relationship between Axis I and Axis II diagnoses of DC/TMD: A cross-sectional survey of dental students - OKAMOTO, Yasuhiro; UCHIDA, Takashi; WAKAMI, Masanobu; KOMIYAMA, Osamu; IIDA, Takashi; MURAMORI, Juri (Journal of the Japanese Society for the Temporomandibular Joint, 2019)
The Diagnostic Criteria for Temporomandibular Disorders (DC/TMD) were determined by clinical examination (Axis I) and psychosocial examination (Axis II), but the relation between Axis I and Axis II has not been investigated. The purpose of this study was to clarify the correlation between Axis I and Axis II with a cross-sectional survey.The subjects were 226 students in the fifth grade of Nihon University School of Dentistry at Matsudo (144 males and 82 females, mean age 23.8±2.7). To make a diagnosis for DC/TMD Axis I, subjective symptoms (Yes: Patient (P) group or No: Normal (N) group) on the examination form and the number of tenderness points on palpation were used. As for Axis II, Oral Behavior Checklist (OBC), anxiety (Generalized Anxiety Disorder-7: GAD-7) and depression (Patient Health Questionnaire-9: PHQ-9) were used. The relation between Axis I and Axis II was examined.A significantly larger number of women had subjective symptoms and tenderness points compared to men, but there was no gender difference in the other variables. There was a significant strong correlation (r = 0.745) between GAD-7 and PHQ-9, and a significant weak correlation (r = 0.322) between OBC and the number of tenderness points. The P group had a significantly higher number of tenderness points and PHQ-9 value compared to the N group. Significant odds ratio was found in the number of tenderness point, slight depression level judged by using PHQ-9, and positive answer in 5th question item of OBC as an independent variable with the presence of subjective symptom as a dependent variable.These results suggest that there is a correlation between Axis I and Axis II diagnoses of DC/TMD in studies using dental students without or with slight symptoms of TMD.